(untitled) (Alberta Journal of Educational Research, 2005)
How does one effectively and ethically conduct research with community members who steeped in histories of economic and social dependency, so that the people themselves charge of their futures? This question is explored in a Canadian context as the authors study the potential of new technologies to bring hope to traditional coastal communities that have been devastated by the collapse of the east coast fishery. Findings highlight the tension inherent in combining traditional knowledge with contemporary "solutions" through technology, as well as the authors’ own ethical participation in suggesting uses the new technology.